The impact of project based-CLIL on students’ english proficiency - Hery Yufrizal (Intelektual Pustaka Media Utama, 2021)
The objective of this article is to explore the effectiveness of a method of teaching English as a foreign language in Indonesian higher institutions called project based Content Language Integrated Learning (CLIL) higher education institutions. The design proposed was based on the principle of language integrated learning (CLIL). Quantitative data were obtained from the scores of students' English proficiency before and after CLIL model application. While the qualitative data were obtained from the output of language produced by students during the learning process took place The results showed that CLIL English language course at higher education institutions in Lampung could work effectively. This is evident from the implementation of the whole program activities, from the implementation of the formation of groups, students work in groups to finish the project, group presentation activities, personal presentations and students’ responses to all activities.